CALCULATED PHASE RELATIONS IN THE SYSTEM NCKFMASH (NA2O-CAO-K2O-FEO-MGO-AL2O3-SIO2-H2O) FOR HIGH-PRESSURE METAPELITES - Wei Ch.; Powell R. (My University, 2006)
Petrogenetic grids in the system NCKFMASH (Na2O–CaO–K2O–FeO–MgO–Al2O3–SiO2–H2O) and the subsystems NCKMASH and NCKFASH calculated with the software THERMOCALC 3.1 are presented for the P–T range 7–30?kbar and 450–680°C, for assemblages involving garnet, chloritoid, biotite, carpholite, talc, chlorite, kyanite, staurolite, paragonite, glaucophane, jadeite, omphacite, diopsidic pyroxene, plagioclase, zoisite and lawsonite, with phengite, quartz/coesite and H2O in excess. These grids, together with calculated compatibility diagrams and P–T and T–XCa and P–XCa pseudosections for different bulk-rock compositions, show that incorporation of Ca into the NKFMASH system leads to many of the NKFMASH invariant equilibria moving to lower pressure and/or lower temperature, which results, in most cases, in the stability of jadeite and garnet being enlarged, but in the reduction of stability of glaucophane, plagioclase and AFM phases. The effect of Ca on the stability of paragonite is dependent on mineral assemblage at different P–T conditions. The calculated NCKFMASH diagrams are powerful in delineating the phase equilibria and P–T conditions of natural pelitic assemblages. Moreover, contours of the calculated phengite Si isopleths in P–T and P–XCa pseudosections confirm that phengite barometry in NCKFMASH is strongly dependent on mineral assemblage.